The Influence of Pontianak Melayu Dialect Towards the Students’ Pronunciation of English Speech Sounds - Meo Nelu, Maria Herlina Wiwin Yuniarti; Mujiyanto, Januarius; Suwandi, Suwandi (English Education Journal, 2021)
This qualitative research attempted to review the influence of the Pontianak Melayu dialect on students’ English pronunciation of English speech sounds. The objectives of the study were to explain the influence of Pontianak Melayu dialect on students’ English pronunciation of vowels, consonants, diphthongs, and consonant clusters and to explain the way teachers play their roles to improve students’ pronunciation. This study used a qualitative case study design. The subjects of this study were 17 students from seventh-grade of Junior High School who are originally from the Pontianak. The data were collected by using questionnaires, students’ recordings, observation checklists, and interviews. The results of this study show that the Pontianak Melayu dialect contributed insignificant positive transfer on English vowel sounds [ɔ:], [ʊ], and [ɒ]. It gave significant negative transfer on English consonant sounds [f, v, k, s]. It also gave insignificant negative transfer on English diphthong sound [aɪ]. It gave significant negative transfer on English consonant cluster sounds [fr] and [kl], and significant negative transfer on three consonant clusters. Meanwhile, the teacher did play her role in improving students’ pronunciation. Based on the findings, it can be concluded that the Pontianak Melayu dialect did not strongly give positive and negative transfer to the students’ English pronunciation. The easiness might be caused by the similarities between the Pontianak Melayu language and English. The difficulties might be caused by the lack of students’ knowledge about correct pronunciation, lack of pronunciation practice, students’ inability to recognize the words, and spelling interference. In teaching pronunciation processes, the teachers and the students should be supported each other to reach the best achievement. The teachers taught by supporting media such as English songs, western movies or English short stories, etc. Meanwhile, the students practice more and more.